Telisik Kisah Tersembunyi dari Makam Kehormatan di Bandung: Ereveld Pandu dan Leuwigajah - Norfaizi, Haris; Hassanah, Delia Nur; Ichsan, Ilham Nur (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
Ereveld is a colonial heritage that still exists today.  This research aims to provide an overview of the Ereveld in Bandung. This research uses historical methods that include heuristics, criticism, and historiography. In Bandung, there are two Ereveld, namely Ereveld Pandu and Leuwigajah. Ereveld is the only land owned by the Dutch Government that still exists and is maintained until now. It is an honorary Dutch burial ground in Indonesia, where perpetrators and victims of the war are buried. Those buried in the Ereveld include Dutch and Indonesian people who were victims during the Japanese occupation. They come from various backgrounds, both military and civilian with various professions. The existence of the Ereveld in Indonesia can still be seen today, and it is well maintained thanks to cooperation between the Dutch and Indonesian sides. Therefore, the Ereveld is a place full of meaning and historical evidence.